Critical heritage studies and the legacies of the late-twentieth century heritage canon. Issue 11 (2nd November 2019) - Gentry, Kynan; Smith, Laurajane
ABSTRACT: In recent years an interest in 'critical heritage studies' (CHS) has grown significantly – its differentiation from 'heritage studies' rests on its emphasis of cultural heritage as a political, cultural, and social phenomenon. But how original or radical are the concepts and aims of CHS, and why has it apparently become useful or meaningful to talk about critical heritage studies as opposed to simply 'heritage studies'? Focusing on the canon of the 1980s and 1990s heritage scholarship – and in particular the work of the 'father of heritage studies', David Lowenthal – this article offers a historiographical analysis of traditional understandings and approaches to heritage, and the various explanations behind the post-WWII rise of heritage in western culture. By placing this analysing within the wider frames of post-war historical studies and the growth of scholarly interest in memory, the article seeks to highlight the limitations and bias of the much of the traditional heritage canon, and in turn frame the rationale for the critical turn in heritage studies.